Status Hukum Khamar dalam Perspektif Fiqh - Winarno, Winarno (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2018)
The verse that talks about the prohibition of drinking khamar in the Alqur'an was gradually reduced in the midst of the ignorant Arab community who had the habit of drinking khamar, getting drunk and to change such conditions in a gradual manner. First, khamar and gambling contain major sins eventhough they contain benefits for humans, but the harm is greater than the benefits. Secondly, it was stated that they were not allowed to pray drunk Third, it is expressly stated that khamar is one of Devil's actions and therefore must be shunned.The scholars differed in defining this khamar. According to Imam Malik, Shafi'i and Ahmad what is meant by khamar is intoxicating drinks, whether or not called khamar. According to Imam Abu Hanifah, it was different from the drunken Khamar drink. But regardless of the definition of the substance is the same, that everything that is intoxicating is a little or a lot of things that are still forbidden.Thus it can be concluded that the prohibition of the khamar does not lie in drunkenness or not, but the location of the substance on the substance. In other words, drinking khamar even if it does not intoxicate the law remains unclean.